Interacciones espaciales en la red urbana: Una discusión sobre los desdoblamientos del proceso de integración sudamericana por medio de las infraestructuras de transportes. - Aparecida Marques de Oliveira Cruz , Dayana (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
The article discusses the redefinition of the role of cities in the urban network from spatial interactions that occur in them and how are reinforced by international integration plans. For this analysis, the article considers the relationship between Brazil and Paraguay in view of the infrastructure works in the road and rail transport proposed by Initiative South American Regional Integration in order to highlight its importance to the Southern Common Market and to Brazil.